2018
DOI: 10.1111/phn.12540
|View full text |Cite
|
Sign up to set email alerts
|

Noise concerns of residents living in close proximity to hydraulic fracturing sites in Southwest Pennsylvania

Abstract: Objective Noise associated with nontraditional gas industry (NTGI) sites (e.g., hydraulic fracturing well pads, compressor stations, processing plants) may create disturbances and anxiety in rural populations. This study evaluated levels of concern among residents of Southwestern Pennsylvania residing near NTGI sites. Design Noise measurements were collected inside and outside residences, and surveys were administered to residents. Results Daytime instantaneous sound levels ranged between 45.0 and 61.0 dBA. Do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
3
0
2
Order By: Relevance
“…More than 17 million people currently live within 1 mi of an oil or gas well in the United States, increasing the potential for exposure to contaminants associated with fossil fuel extraction (Czolowski et al 2017). The potential health hazards associated with OGD activity include contamination of air (Adgate et al 2014;Shonkoff et al 2014;Werner et al 2015) and water (Jackson et al 2013) by hazardous chemicals and increased psychosocial stress as a result of noise, increased seismic activity, and social hazards associated with disruptions to the local social fabric (Allshouse et al 2019;Richburg and Slagley 2019;Witter et al 2013;Adgate et al 2014). Fracking involves the injection of fluids, sands, and chemical additives into wells to reduce friction, decrease drill time, or stimulate production and include chemicals that are known carcinogens, mutagens, reproductive and developmental toxins, or endocrine disruptors (Webb et al 2014;Kassotis et al 2016;Yost et al 2016;Stringfellow et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 17 million people currently live within 1 mi of an oil or gas well in the United States, increasing the potential for exposure to contaminants associated with fossil fuel extraction (Czolowski et al 2017). The potential health hazards associated with OGD activity include contamination of air (Adgate et al 2014;Shonkoff et al 2014;Werner et al 2015) and water (Jackson et al 2013) by hazardous chemicals and increased psychosocial stress as a result of noise, increased seismic activity, and social hazards associated with disruptions to the local social fabric (Allshouse et al 2019;Richburg and Slagley 2019;Witter et al 2013;Adgate et al 2014). Fracking involves the injection of fluids, sands, and chemical additives into wells to reduce friction, decrease drill time, or stimulate production and include chemicals that are known carcinogens, mutagens, reproductive and developmental toxins, or endocrine disruptors (Webb et al 2014;Kassotis et al 2016;Yost et al 2016;Stringfellow et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…2013 ) by hazardous chemicals and increased psychosocial stress as a result of noise, increased seismic activity, and social hazards associated with disruptions to the local social fabric ( Allshouse et al. 2019 ; Richburg and Slagley 2019 ; Witter et al. 2013 ; Adgate et al.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies document sociopsychological impacts in residents living near UOGD sites due to anxieties related to the potential release of toxins and carcinogens [36]. Commonly reported symptoms from those living near UOGD included psychosocial stress associated with community change [23], worry [37,38] and adverse mental [39] and physical health effects [40]. As UOGD outpaces the scientific community's ability to understand potential health effects, studies of self-reported outcomes are a vital way to understand health impacts in order to influence public policy [40].…”
Section: Human Health Impacts and Proximity To Uogdmentioning
confidence: 99%
“…Así, según lo reportado por Habicht, Hanson y Faeth en las plataformas durante el fraccionamiento el ruido llega a superar los 100 decibeles (dB) [42]; además durante más de dos meses se mantienen ruidos de aproximadamente 60-80 dB. En [2] se reporta la medición de ruido en las zonas de fracking en el suroeste de Pensilvania. En este estudio se constató que los niveles de sonido instantáneo durante el día oscilaron entre 45.0 y 61.0 dBA, mientras los dosímetros registraron niveles díanoche de 53.5-69.4 dBA en espacios abiertos y de 37.5-50.1 dBA en espacios cerrados.…”
Section: Contaminación Sonora Por Frackingunclassified
“…Varias publicaciones señalan que la aplicación del fracking tiene un alto potencia de causar contaminación ambiental; principalmente se le acusa de producir ruido [2], facilitar la emisión de la superficie de gases del subsuelo [3], de contaminar el aire [4] y de generar contaminación del agua y el suelo por lagunas de aguas residuales de extracción.…”
Section: Introductionunclassified